2020
DOI: 10.1016/j.mehy.2020.110140
|View full text |Cite
|
Sign up to set email alerts
|

The possible immunoregulatory and anti-inflammatory effects of selective serotonin reuptake inhibitors in coronavirus disease patients

Abstract: While researchers are struggling to develop a vaccine for coronavirus disease, it is important to evolve effective therapeutic strategies to save lives. The majority of coronavirus disease deaths are due to pneumonia. Mostly, stress and depression are associated with coronavirus disease infection and thus, resulting in weakening of patients’ immune response and hence, more severe respiratory symptoms or even death. We propose using a class of antidepressants named selective serotonin reuptake inhibitors for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 52 publications
0
41
0
1
Order By: Relevance
“…Maprotiline, a TCA, structurally different from other TCAs, had a strong negative connection in our analysis. Antidepressants such as TCAs and selective serotonin reuptake inhibitors have previously reported antiviral, immunomodulatory effects and antioxidant properties [ 65 ]. Although data are limited on the innate and adaptive immune effects of TCAs, they appear to have anti-inflammatory effects detected via TNF-α and IL-6 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maprotiline, a TCA, structurally different from other TCAs, had a strong negative connection in our analysis. Antidepressants such as TCAs and selective serotonin reuptake inhibitors have previously reported antiviral, immunomodulatory effects and antioxidant properties [ 65 ]. Although data are limited on the innate and adaptive immune effects of TCAs, they appear to have anti-inflammatory effects detected via TNF-α and IL-6 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no clinical study has been done with a view to correcting the 5-HT deficiency of coronavirus patients as the possibility of such 5-HT deficiency has not been considered earlier. Nevertheless, on the basis of the existing knowledge that some SSRIs have anti-inflammatory, antiviral, immunoregulatory and neuroprotective properties, a few studies [114] , [115] , [116] , [117] , [118] have been carried out to explore the effect of SSRIs on the coronavirus patients, where SSRIs like fluvoxamine, fluoxetine and escitalopram have been found to somewhat decrease the severity of COVID-19. This observation is in line with the present hypothesis, though, as anticipated from the hypothesis, a significant improvement is lacking.…”
Section: Implications and Importance Of The Hypothesismentioning
confidence: 99%
“…About 40% of the patients treated in the critical care unit display an acute respiratory distress syndrome associated with pneumonia (Guan et al, 2020). In summary, COVID-19 may lead to overstimulation of the immune system (Giamarellos-Bourboulis et al, 2020) and it has been suggested that inhibition of serotonin reuptake may reduce exacerbated inflammation (Hamed and Hagag, 2020). Remarkably, this hypothesis has been supported by a recent study reporting less risk of intubation or death in patients taking antidepressant medication (Hoertel et al, 2021).…”
Section: Atpmentioning
confidence: 96%